1978
DOI: 10.2135/cropsci1978.0011183x001800050032x
|View full text |Cite
|
Sign up to set email alerts
|

Selection for Acetylene Reduction Rates in ‘Mesilla’ Alfalfa1

Abstract: The rate of N fixation by leguminous plants depends on both the effectiveness of the Rhizobium strain and the genotype of the host plant. Most of the previous work has involved attempts to improve the bacterial strain. The objective of this study was to determine the variability in ‘Mesilla’ alfalfa (Medicago sativa L.) for plant characteristics considered to be indices of N fixation and to determine the response of these indices to selection based on acetylene reduction rate. Alfalfa seedlings were grown for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1981
1981
1992
1992

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…838. 83 Tonn and Weaver, 1981). Despite these shortcomings, observations of acetylene reduction activity (ARA) on groundnuts (grown in conditions of limited soil N) can correlate well with final N accumulation (Arunachalam et al, 1984;Dutta et al, 1988), suggesting that this method can provide a quantitative index of N2 fixing ability for use in breeding programs (Coale et al, 1985;Duhigg et al, 1978;Graham and Temple, 1984). Usually the described genotype variations in ARA are based on isolated plants, or on plants in widely spaced rows, i.e., conditions where the fraction of incoming light intercepted by the crop is less than one.…”
Section: Introductionmentioning
confidence: 99%
“…838. 83 Tonn and Weaver, 1981). Despite these shortcomings, observations of acetylene reduction activity (ARA) on groundnuts (grown in conditions of limited soil N) can correlate well with final N accumulation (Arunachalam et al, 1984;Dutta et al, 1988), suggesting that this method can provide a quantitative index of N2 fixing ability for use in breeding programs (Coale et al, 1985;Duhigg et al, 1978;Graham and Temple, 1984). Usually the described genotype variations in ARA are based on isolated plants, or on plants in widely spaced rows, i.e., conditions where the fraction of incoming light intercepted by the crop is less than one.…”
Section: Introductionmentioning
confidence: 99%
“…The most striking variation has resulted in decreased nodulation or absence of nodulation (8). Nevertheless, variants within existing germ plasms with increased nodulation have been demonstrated in some species (9)(10)(11)(12)(13)(14)(15). These promising variants with enhanced nodulation have previously been selected in the absence of nitrate (9,15).…”
mentioning
confidence: 99%
“…Similar results had been reported previously 14. Seetin and Barnes a~ , Duhigg et al 4 and Tan ~3 showed that acetylene reduction rate and other characters associated with nitrogen fixation in alfalfa were genetically controlled. Tan and Tan is further reported that a large portion of the genetic variation for acetylene reduction rate was attributed to the interaction between alfalfa cultivars and Rhizobium strains.…”
Section: Resultsmentioning
confidence: 99%